A RESEARCH OF ADOLESCENTS PHYSICAL ACTIVITY DURING THEIR FREE TIME IN CITY OF PLOVDIV, BULGARIA - Elena Merdzanova; Gergana Petrova; Hristina Kulina; Valentina Lalova (Peytchinski Publishing, 2019)
Purpose: The research aimed to study children's physical activity during their free time and their attitude towards sports as well as to analyze of their nutrition habits in relation to the determination of adolescents' BMI (body mass index). Materials and methods: Sociological and statistical methods have been used. The students' BMI was estimated through the index method. The results have been processed with the program package IBM SPSS Statistics 21. The method of classification and regression trees (CART) has been applied to define the factors influencing BMI. The research objects have been 275 students from 5th, 6th, 7th, and 8th grade from secondary schools in Plovdiv. Results: The share of those who have breakfast in the morning (50,2 %) was almost the same as those who had more than two main meals per day (53,8 %). From all respondents, almost a quarter was not interested in sports, which was also confirmed by the fact that 39,3 % of the respondents did not practice sports after school. The BMI estimation (according to the WHO standards) provided the following results: 60 % of the adolescents had normal weights, and 38,5 % had weight over the norm. Conclusion: Unhealthy and not - balanced nutrition habits were found at almost half of the examined students. This nutrition was accompanied by insufficient physical activity - the share of 11-12 years old students with overweight is bigger than those of 13-14 years old.